MULTIMEDIA APPLICATIONS AND VIDEO MP3 PLAYER USING BORLAND DELPHI 7 - Setiawan Priatmoko; Ristyawati SKom , MMSI (Jurnal Sistem Informasi, 2007)
Applications Multimedia Music And Video Player is an application that is created asa complement to one among multimedia applications multimedia applications thathave been there earlier that aims to provide an overview on how to manufacture andease of Multimedia Applications and Video MP3 Player used as a means of learningand useful information for the general public. by presenting in the form ofapplications using Borland Delphi 7.